The Effect of Concentration of NaOH and H2SO4 on Isolation and Identification of Cellulose Using The Delignification Process of Water Hyacinth Powder (Eichhornia crassipes) - Yulianita Pratiwi Indah Lestari; Nita Triadisti; Irfan Zamzani (JCPS (Journal of Current Pharmaceutical Sciences), 2021)
The effect of concentration of NaOH and H2SO4 in cellulose isolation by delignification process from water hyacinth powder has been investigated to reduce lignin content. Delignification was carried out at 121⁰C for 30 minutes with variations in NaOH concentration being 0%, 2.5%, 5.0%, 7.5%, and 10% (w/v), while the variation of H2SO4: 0% , 0.5%, 1.0%, 1.5%, and 2.0% (v/v). The decrease in lignin content was analyzed based on the remaining cellulose content. The increase in the concentration of NaOH and H2SO4 was in line with the decrease in the amount of cellulose obtained. The biggest decrease was in NaOH 10% with cellulose yield of 32,66% and H2SO4 2.0% with cellulose yield of 42,00%.